PALYNOSTRATIGRAPHIC SUBDIVISION AND CORRELATION OF PALEOGENE-MIOCENE DEPOSITS IN THE AMGUN-GORIN REGION (MIDDLE COURSES OF THE AMUR RIVER) - Baskakova L.A. (My University, 1997)
Palynological data are used for the first time to subdivide in detail the Paleogene-Miocene deposits filling intracontinental depressions in the Amgun-Gorin region. Twelve pollen assemblages are distinguished in the composite section (middle Eocene-upper Miocene) studied and divided into respective biostratigraphic units of local significance indicated as palynofloral beds. Lithological and palynological data obtained show that the main part of the section comprising the interval from the mid-middle Eocene to the lower Miocene correlates well with coeval deposits in adjacent areas and thus suggests that the whole Far East region was controlled by a common trend of the Cenozoic geological evolution. Two stratigraphic intervals above the coal-bearing beds (in the middle and terminal upper Miocene) are lacking pollen remains, and this presumably points to local breaks in sedimentation.
Keywords: Miocene; Paleogene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene; Cenozoic::Neogene::Miocene; Кайнозой::Палеоген